A Study of Some Demographic Factors and Blood Parameters to Pregnancy and Abortion Women in Education Hospital of Women and Children/ Al-Qadisiya Province - K. Al-Mayali, Hussein; S. Edan Al-Musawi, Zahra (Al-Qadisiyah Journal of Pure Science, 2018)
The current study was conducted in Al-Diwaniyah city/ Al-Qadisiya Province/ Iraq, to know the changes in some demographic factors and blood parameters associated with pregnant women and abortifacients, and compared with normal women (control). The study was designed according to the 80 patient women to education hospital of women and children in Al-Diwaniyah city/ Al-Qadisiya province, and distributed among the 20 women of the control group and the like for a group of pregnancy and doubled to abortion group; for two reasons: the first is represents the main study group and the most obvious in terms of changes in blood parameters, and the second is to ensure the inclusion of a wider community of the sample. All analyzes under study were carried out in the same hospital laboratories above. Results showed that recording of miscarriages higher by demographic factors (age, weight, height and BMI), although there are no differ significantly from the control group (P>0.05) as much supremacy moral pregnancy group (P<0.05) in above mentioned parameters except height feature were not show significant to all groups with all same (P>0.05). Blood parameters were recorded a significantly superior to control group in PCV, Hb and RBC compared with pregnancy and abortion groups and abortion group were superior in WBC and ESR compared with group of control and pregnancy, respectively.